Pemanfaatan Media Sosial dalam Kampanye Digital #WasteDownBeautyUp oleh Sukin dan Sociolla - Muhammad Iqbal; Zefanya Atmaja Nugraha (Lembaga Pengembangan Kinerja Dosen, 2023)
This research aims to investigate the utilization of social media as a marketing communication tool by one of Sukin’s skincare products, which collaborates with an e-commerce platform and social media focused on beauty and skincare. The research employs a qualitative method involving observation and interviews. Data collected are analyzed using The Circular Mode of SoMe analysis model, which includes elements such as Share, Optimize, Manage, and Engage. The results indicate that Sukin and Sociolla utilize social media platforms effectively to introduce their beauty and skincare products, serving as communication tools for marketing purposes. Additionally, audiences participate in word-of-mouth promotions, provide reviews as beauty enthusiasts, and even involve influencers in digital campaigns created by Sukin and Sociolla. The evolution of social media usage across various fields facilitates easier communication and message delivery, contributing to the objectives of digital campaigns.